Bilingualism and Musicianship Enhance Cognitive Control - Scott R. Schroeder; Viorica Marian; Anthony Shook; James Bartolotti (Neural Plasticity)
Learning how to speak a second language (i.e., becoming a bilingual) and learning how to play a musical instrument (i.e., becoming a musician) are both thought to increase executive control through experience-dependent plasticity. However, evidence supporting this effect is mixed for bilingualism and limited for musicianship. In addition, the combined effects of bilingualism and musicianship on executive control are unknown. To determine whether bilingualism, musicianship, and combined bilingualism and musicianship improve executive control, we tested 219 young adults belonging to one of four groups (bilinguals, musicians, bilingual musicians, and controls) on a nonlinguistic, nonmusical, visual-spatial Simon task that measured the ability to ignore an irrelevant and misinformative cue. Results revealed that bilinguals, musicians, and bilingual musicians showed an enhanced ability to ignore a distracting cue relative to controls, with similar levels of superior performance among bilinguals, musicians, and bilingual musicians. These results indicate that bilingualism and musicianship improve executive control and have implications for educational and rehabilitation programs that use music and foreign language instruction to boost cognitive performance.